PROFESSIONAL PEDAGOGICAL MOBILITY AND SPECIFIC FEATURES OF ITS FORMATION - Aidarov, B.J.; Tankish, N.P.; Utegenov, B.D. (Scientific Journal of Pedagogy and Economics, 2020)
Researching the content of the issue of professional and pedagogical mobility, we note the following. At the present stage of development of modern society, the problem of professional and pedagogical mobility is especially relevant. It is characterized by the growth of intensive and progressive changes in society, covering all spheres of human life, including the professional sphere. For a modern specialist to be successful and necessary, he must be mobile, ready for changes, able to quickly adapt to changing conditions, that is, he must be professionally mobile. Great importance is attached to the consideration of professional and pedagogical mobility as a pedagogical category. Concepts such as "mobility", "professional mobility", "pedagogical" are analyzed. On the basis of research and supplementation of these concepts there is a problem of independent understanding of professional and pedagogical mobility as a characteristic of the individual, which is reflected in the process of professional activity, readiness to develop, self-structuring and adapt to changes in the changing professional environment. The article clarifies the need to create a personal professional image, to organize and implement practical activities to get closer to this person, to detail the main steps for reorganization in connection with the changing conditions of the professional and pedagogical environment.